Análises das políticas públicas que impulsionaram a industrialização da Coréia do Sul: lições para o Equador - Romero, Fernanda Sofía Mideros (2017)
In the last decade, Ecuador has achieved political, social and economic stability. The State has made great efforts to lead the country into a process of industrialization and development, taking as an example the successful process of South Korea. However, although it has improved in several aspects, still has the weaknesses it had long before the State started with this initiative. To contribute to this debate, the main objective of this study is to understand the factors that drove South Korea's accelerated industrialization and development; and to verify if it is possible to use them as a reference in Ecuador's development process, considering the cultural, political, social, economic and historical differences between the two countries. To achieve this goal, a three-phase methodology was performed: the first was a quantitative correlation analysis and the Vector auto regression (VAR) model of the policies considered important in South Korea's industrialization and development; in the second phase a bibliographic and documentary research was developed on the educational and industrial policies implemented in Ecuador. From these results, the third phase was elaborated, in which the conditions and factors that enabled the success of policies in South Korea were identified. These factors are the leadership role of the state; the combined model of import substitution and the promotion of exports; the importance attributed to education, technology and science; and the relationship of "Embedded Autonomy" of the government with private enterprise. The conditions: Adequate levels of social equality, high degree of consensus and social cohesion, the structure and favorable attributes of public administration (made possible mainly by the low interference of pressure groups). Finally, these factors and conditions were discussed into possible lessons for the current Ecuadorian reality.